Predictive value of complete blood cell count-based inflammatory markers for peritonitis risk in peritoneal dialysis patients: A multicenter cohort study - Xue Li; Wenlong Qiu; Qingdong Xu; Yueqiang Wen; Xianfeng Wu; Xiaojiang Zhan; Fenfen Peng; XiaoYang Wang; Juan Wu; Ning Su; Xiaoran Feng; Xingming Tang; et al. (PLoS ONE, 2026)
Background Peritonitis is a serious complication of peritoneal dialysis (PD). Inflammatory indices derived from routine complete blood count (CBC) parameters—including the pan-immune inflammatory value (PIV), systemic immune-inflammatory index (SII), platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), and platelet-to-monocyte ratio (PMR)—have shown prognostic value in various diseases. However, their comparative utility in predicting PD-associated peritonitis (PDAP) remains unclear. This multicenter cohort study aimed to evaluate and compare these indices to identify the best predictor of PDAP. Methods We retrospectively enrolled 2,036 PD patients from 10 centers. The associations between inflammatory markers (PIV, SII, PLR, NLR, MLR, PMR) and peritonitis risk were analyzed using restricted cubic splines. Optimal cut-offs were determined by ROC analysis. Survival differences were assessed using Kaplan–Meier curves and log-rank tests. Independent predictors were identified via multivariate Cox regression, with model discrimination evaluated by the C-index. Subgroup analyses were conducted by gender, age, body mass index (BMI), diabetes, albumin, PD vintage, and residual renal function. Results The median age was 51.0 years, 55.01% were male, and median dialysis vintage was 49.47 months. Diabetes prevalence was 21.02%. Over the follow-up, 147 patients (7.22%) developed peritonitis. Among the indices evaluated, PIV, SII, and PLR showed significant nonlinear associations with peritonitis risk (all P < 0.05). Adjusted hazard ratios were 2.004 for PIV, 2.144 for SII, and 2.063 for PLR. Adjusted C-indices were 0.67 (PIV), 0.70 (SII), and 0.70 (PLR). No significant interactions were found in subgroup analyses. Conclusion Elevated PIV, SII, and PLR levels at PD initiation independently predict higher peritonitis risk. Although their discriminative ability is moderate, these routine, cost-effective indices may aid risk stratification and help identify patients needing closer monitoring or preventive interventions.